Pengaruh Asset Tangibility, Profitability, dan Growth Terhadap Leverage Saat Pandemi Covid-19 - Riska Tiara Putri; Agrianti Komalasari; Widya Rizki Eka Putri (Goodwood Publishing, 2022)
This study aims to examine the effect of asset tangibility, profitability, and growth on leverage which is reflected in the debt to asset ratio (DAR). This study used a sample selection method which was carried out using a purposive sampling method. This study uses a data sample of 57 infrastructure, utilities, and transportation companies listed on Indonesia Stock Exchange for period 2020-2021. The analysis statistic utilized to test the hypothesis is multiple linear regression analysis. The test showed that statistically the independent variable asset tangibility, profitability, and growth simultaneously have positive and significant effect on leverage. The testing partially asset tangibility has a positive effect on leverage, profitability had a negative effect on leverage. While the independent variable growth had no effect on leverage.